Hepatocellular Carcinoma in a Patient With Hepatic Steatosis. Issue 5 (5th May 2020) - Romano, John; Forster, Erin
ABSTRACT: Hepatocellular carcinoma (HCC) has historically developed in the setting of known risk factors—chronic liver disease from viral hepatitis and cirrhosis. In the absence of a risk factor, the development of HCC was rare. However, the increasing prevalence of nonalcoholic liver disease and nonalcoholic steatohepatitis, the paradigm is shifting. Currently, no HCC screening guidelines exist for these patients. We report a 30-year-old man with a medical history of treated nonseminomatous germ cell testicular cancer who presented with asymptomatic transaminitis. Subsequent workup was notable for a 1.6-cm liver lesion. The patient underwent a left lobe wedge resection with pathology demonstrating a well-differentiated HCC in a background of hepatic steatosis.